Enhancing the Performance of AODV by Exchanging Neighboring Node Information with Hello Packets in VANET (International Journal of Engineering and Computer Science, 2016)
Today's developing innovation of wireless communication is a Vehicular Ad-hoc Network (VANET). VANET is an instance of MANET in which the foundation of wireless scenario is done between vehicles-vehicles and vehicles-roadside Unit (RSU) [12]. Mobile nodes in VANET are considered as quick moving vehicles because of which the topology turns out to be very dynamic in nature, which makes it exceedingly supportable for analyzing the security measures for drivers and travelers if there should be an occurrence of any perilous circumstance. AODV is a reactive routing protocol, which has critical influence in the route discovery from source to destination. In this paper, we have acquainted an enhanced strategy with lessening the overhead of control messages from the network by sharing the information through HELLO messages, and expansion the execution of AODV in VANET environment